George E. Tinker, Spirit and resistance. Political Theology and American indian liberation, Minneapolis, Fortress Press, 2004, 144 pp. - Caamaño, José Carlos (2007)
Fil: Caamaño, José Carlos. Investigador independiente: Argentina